PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PP. PROPERTI, TBK PROYEK BEGAWAN KOTA MALANG - Moh Uwais Al-Qorni; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research was conducted for knowing how much the effect of leadership style, communication, and work environment to the performance of PT. PP. Properti, Tbk Project Begawan Malang Employees. In order to know how much the effect of independent variables toward dependent variable either partially or stimultaneously, this research was conducted with several methods in data examining. The result was that leadership style, communication, and work environment had stimultaneously a directly proportional and gave positive effect and the most significant effect of those three variables toward employees performance was communication. It can be showed from the value of two other variables which were lower. While independent variable showed a directly proportional and gave positive and significant effects, except leadership style (X1). Keywords: Leadership Style, Communication, Work Environment, and Employee Performance.